RO film-based pretreatment method for tritium determination by LSC. (December 2020) - Li, Gang; Liang, Manchun; He, Shuijun; Liu, Jiacheng; Pang, Xinxin; Zeng, Zhengkui
Abstract: Tritium analysis in water is an important part of environmental radiation monitoring. At present, tritium in water is generally measured by liquid scintillation counting (LSC). To optimize the pretreatment process and improve the efficiency of tritium analysis via LSC, a pretreatment device for tritium analysis in water based on a reverse osmosis (RO) film was developed. This paper introduces the system composition and carries out the following experimental studies: First, the comprehensive performance of the device was studied by performing repeated analyses, and the pretreatment time can be reduced by approximately 77% compared with that of the traditional method; then, the device was used to process tritium samples with different concentrations to verify the negligible impact of any tritium residue in the RO film; finally, the reliability of the results is verified by comparing with the traditional atmospheric distillation pretreatment method under the same measurement conditions. The results showed the developed method has the advantages of a simple operation and a high degree of automation, which effectively improves the efficiency of tritium analysis in water. Highlights: A new method for pretreatment of tritium in water was presented and shortens the pretreatment time by more than 77%. Compared with that of a traditional pretreatment method, the accuracy of tritium measurement after use of the developed pretreatment method is more consistent. In this method, an RO film is used for pretreatment. For environmental water samples, the influence of residual tritium on the RO film can be ignored. This method can be used to automatically preprocess water samples for tritium analysis and provide a reliable choice for the automation of tritium measurement.